(untitled) (The Research of Medical Science Review, 2025)
Background: According to the World Health Organization 2016 disease assessment report, cardiovascular diseases are the leading cause of death for the last ten years. Therefore, treatment of CVDs is very necessary to minimize the mortality and improve the quality of life of the population been affected. So cardiac rehabilitation is one of the best Service to improve the quality of life of the cardiac patients. Moreover, as nurses are the key health care providers so they must have sufficient knowledge regarding cardiac rehabilitation programs. Results: The data was analyzed by SPSS version 26.0, different statistical tests like ANOVA and Chi Square were used. knowledge among nurses was categorized to poor (6.8%) good (65.9%) and very good (27.7%). Mostly the attitudes of the participants were found poor and unsatisfactory, while most of them held responsible the policymakers to initiate cardiac rehabilitation programs in Pakistan. Conclusion and recommendations: As the study highlighted that knowledge of the nurses was satisfactory but instead needs further programs to develop their attitudes and practices regarding the benefits of the programs so that to ensure the high efficacy in this concern because through such programs one can reduce the morbidity and mortality of a society due to cardiovascular diseases.